Form and Function in Information for Visual Perception. (November 2021) - Lappin, Joseph S.; Bell, Herbert H.
Visual perception involves spatially and temporally coordinated variations in diverse physical systems: environmental surfaces and symbols, optical images, electro-chemical activity in neural networks, muscles, and bodily movements—each with a distinctly different material structure and energy. The fundamental problem in the theory of perception is to characterize the information that enables both perceptual awareness and real-time dynamic coordination of these diverse physical systems. Gibson's psychophysical and ecological conception of this problem differed from that of mainstream science both then and now. The present article aims to incorporate Gibson's ideas within a general conception of information for visual perception. We emphasize the essential role of spatiotemporal form, in contrast with symbolic information. We consider contemporary understanding of surface structure, optical images, and optic flow. Finally, we consider recent evidence about capacity limitations on the rate of visual perception and implications for the ecology of vision.